Davimacrocera, a New Extant Genus of Keroplatidae, with Notes on the Fossil Genus Burmacrocera (Diptera) - Jan Ševčík (Insects)
A new extant genus of Keroplatidae (Diptera: Bibionomorpha), Davimacrocera gen. nov., is described in this paper, which includes two new species, Davimacrocera davidi sp. nov. (Brunei, type species of the genus) and D. taiwanensis sp. nov. (Taiwan, China). Its relationships to other extant genera and possible phylogenetic position are briefly discussed, including a comparison with the fossil genus Burmacrocera Cockerell, 1917 from the mid-Cretaceous amber of Myanmar. The identity of Burmacrocera remains unclear, pending further studies of Keroplatidae in Burmese amber.